Analisis Pengaruh Temperatur Terhadap Sifat Termal dan Gugus Fungsi Proses Thermoforming Material Polivinilklorida - Budiarto Djono Siswanto; Bayu Fajar Saputro; Melya Dyanasari Sebayang (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2021)
Forming sheet plastic into various new shapes and applications, this plastic is adjusted to the design we want with the help of heat, pressure and molding. The purpose of this study was to determine the energy and heat value released by PVC material with variations in heating and cooling temperatures in the forming unit,to determine the effect of PVC process temperature on thermal properties with DSC tools and to determine the effect of PVC process temperature on functional groups using FTIR tools.The calculation results show that the heat released by the A.1 material is 1,740 Watt and A.2 is 1,938 Watt. The energy received by the cooling water in the 30th minute on specimen A.1 is 5.571 Watt and A.2 is 14,857 Watt with each temperature increase of 0.5℃. The results of the DSC test samples A.1 (defective) and A.2 (good) show that the melting temperature of the two is almost the same, which is around 78oC but there is a difference in Tg (temperature glass) of 0.013 J/goC faster than the A.2 test specimen 115oC (Very nice). The results of the FTIR test samples A.1 (disabled), A.2 (good) showed the highest difference in wavelength up to 8.4% at the wave values of 3749.77cm-1 and 3740.90cm-1.